Development and Validation of Creative Thinking Instruments and PjBL-E-Module Assessments for Pre-Service Physics Teachers - Gunawan Gunawan; Kosim Kosim; Nina Nisrina; Ahmad Busyairi (Indonesian, 2025)
This study aims to elucidate the development process and validate the research instruments and learning materials employed in a study investigating the enhancement of creative thinking skills in pre-service physics teachers through a Project-Based Learning (PjBL) model integrated with e-modules. The validated components include a creative thinking test instrument (measuring fluency, flexibility, elaboration, and originality), a PjBL creative process assessment instrument, a creative product assessment rubric (for videos, websites, games, and posters), and the design of the e-module and its supporting media. The validation process was conducted by three expert validators who evaluated aspects of content, construct, language, and technicality. Validation results revealed overwhelmingly positive assessments, with average scores for all instruments and materials falling into the 'very good' category (ranging from 4.33 to 5.00 on a 5-point scale). Specifically, the creative thinking test instrument was highly rated for its alignment with creativity indicators; the creative process assessment sheet was deemed detailed and systematic; the creative product rubric achieved perfect scores for objective evaluation; and the e-module was judged highly engaging and effective in facilitating self-regulated learning integrated with PjBL syntax. These findings affirm that the developed instruments and learning materials possess high validity and are ready for accurate and comprehensive measurement and facilitation of creative thinking skills in pre-service physics teachers.